Distance learning: methodics, potential, avantages and disadvantages - Cherednichenko, Galina; Shapran, Ludmila; Чередніченко, Галина Анатоліївна; Шапран, Людмила Юліївна (My University, 2013)
In the article the authors disclose concept, characteristics, peculiarities of distance learning, which is gaining popularity around the world. In Ukraine, distance education is extremely actual. The reason for this success lies in regular training and retraining, as well as distance education is an alternative to extramural courses. The authors analyze theoretical, legal and methodological resources of distance education, reveal the advantages and disadvantages, problems and prospects of implementing distance education in Ukraine.
Keywords: data portal; FOOD-INFO; european project; інформаційний портал; європейський проект; информационный портал; европейский проект; кафедра ділової іноземної мови та міжнародної комунікації